1980
DOI: 10.3382/ps.0591995
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Reproductive Development Resulting from Aflatoxicosis in Juvenile Japanese Quail

Abstract: Aflatoxicosis was induced in young Japanese quail. In the first experiment five replicates of 30 birds per treatment were fed a soy-corn basal ration containing 0, 5, or 10 microgram aflatoxin per gram of feed from 1 to 3 weeks of age. At 3 weeks, the animals were sacrificed and mesurements taken. In the second experiment, 0 to 10 microgram aflatoxin per gram of diet were fed from either 1 to 3 weeks of age or 2 to 4 weeks of age. At 3 weeks of age body weights were significantly (P < .05) reduced and relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…One of the earliest studies indicating morbidness of reproductive efficiency due to AF toxicity was done by Maryamma and Sivadas (1975) who reported that continuous feeding of a diet containing 0.7 ppm AF produces testicular degeneration in male goats. There have been other reports which indicate that AFB1 causes delay in physiological and behavioral sexual maturation and also delays testicular development in Japanese quail (Doerr and Ottinger, 1980). It has been additionally discovered that AFB1 decreases semen volume and testis weight and leads to the disruption of the germinal epithelium in mature male white Leghorn chicks (Sharlin et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…One of the earliest studies indicating morbidness of reproductive efficiency due to AF toxicity was done by Maryamma and Sivadas (1975) who reported that continuous feeding of a diet containing 0.7 ppm AF produces testicular degeneration in male goats. There have been other reports which indicate that AFB1 causes delay in physiological and behavioral sexual maturation and also delays testicular development in Japanese quail (Doerr and Ottinger, 1980). It has been additionally discovered that AFB1 decreases semen volume and testis weight and leads to the disruption of the germinal epithelium in mature male white Leghorn chicks (Sharlin et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that enzyme induction could increase aflatoxin detoxification was of interest because aflatoxins are relatively common contaminants of poultry feed, with capability of reducing weight gain, feed efficiency, reproductive performance, and resistance to disease (Edds and Bortell, 1983;Doerr and Ottinger, 1980). We, therefore, conducted the present investigation to determine if aflatoxin toxicity in chicks could be modified in the presence of BHT, a synthetic antioxidant commonly used as a feed preservative.…”
Section: Introductionmentioning
confidence: 98%
“…Japanese quail: Sawhney et al, 1973). Moreover, a¯atoxin decreased ovarian follicular development in young Japanese quail (Doerr and Ottinger, 1980). Treatment of male chickens with a mixture containing a¯atoxin reduced a number of indices of reproductive function.…”
Section: Mycotoxinsmentioning
confidence: 97%